Grain dockage in harvesting operations: how to avoid it? - Kurdyukova, O.N.; Storchous, I.N.; Tyschuk, O.P. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
It determined some features of the species and quantity compositions of weed seeds in the grain mass of the dominant major field crops of the steppe and forest — steppe zones of Ukraine at the harvesting time. It identified the main sources of weed seeds entrain the grain mass, depending on the harvesting time and the contamination degree of spiked cereals, cereal crops and tilled crops plantings.